An assessment of the project management of DOST SETUP implementation in DOST XI - Dado, Maria Victoria Itucas (University of the Philippines Diliman, 2012)
The aim of this study was to assess the project management of the Small Enterprise Technology Upgrading Program (SETUP) project implementation by DOST Regional Office No. XI. Generally, the objective of this study was the examination of the project's cycle time vis-a-vis the process elements and performance of the SETUP implementation in the region. The study had likewise identified, through proper assessment, the best management practices employed in the region. The study further assessed and looked into the elements of SETUP implementation process that hindered it from reaching out to a larger number of existing MSMEs within the region. The study eventually came up with recommendations on the project management process that could be used by the DOST system to increase productivity and reduce risks on the part of the implementers. Respondents in this study were beneficiaries of the SETUP project in the region - those who were already approved and those who are "on process" status for the period starting 2007 until 2011. For this project, quantitative research method was employed by the researcher. The survey questions were formulated in a way that they were partially open-ended so as to encourage the respondents to give their views and opinions on certain questions. To validate and support the data gathered through the survey questions, interviews of the forty-six (46) SETUP beneficiaries were conducted by the researcher in coordination with the City and Provincial S&T Directors. The profiling of the estimated cycle time of SETUP process elements were based on SETUP documents gathered by the researcher from the Regional Program Management and Operations (RPMO). In the process, the researcher closely coordinated with the provincial staff, regional office and the technical services division where the RPMO was under supervision by the Assistant Regional Director. This provided the researcher full access to the files of each project SETUP beneficiary. Thus, the researcher was able to review the historical and current data of each project beneficiary. The data gathered by the researcher, particularly those related to the dates of submission, dates of RTEC visits, dates of RTEC reports, dates of endorsement to NPMO, dates of notice of approval or disapproval and dates of signing of MOA or MOI before project implementation, were necessary for the profiling and for the establishment of the cycle time and turnaround time from 2007 until 2011. Verification and clarification of data of SETUP beneficiaries were also done between the researcher and the RPMO staff, City/Provincial S&T Directors and the beneficiaries. This study presents a descriptive analysis of the critical issues identified from the validation process so as to effectively address matters pertaining to overall program management. Assessment scores of the Criteria for Performance Excellence (CPE) and its system maturity level were utilized in the analysis of data. Results show that there is a significant change in the project management process in terms of cycle time and turnaround time from 2007 to 2011. In 2007 it took almost 24 months of processing time for a project to be approved by the NPMO. In 2011, the processing time was reduced to 1.65 months. The established processing time in 2007 was attributed to lack of systematic approach being employed in the process. Adoption of management standards pursuant to ISO 9001 : 2000/2008 contributed significantly to the considerable reduction of the processing time. Management leadership in the SETUP was also a major factor on the significant reduction of the processing time. The Regional Director made sure that the processes employed were reviewed constantly in order to improve the service and to maintain a QMS in conformity with ISO 9001:2008. The result of the study further shows that the level of maturity of project implementation in the region had significantly increased from 2007 up to 2011. This major improvement in the level of maturity of the process only reaffirms that the learnings and the effectiveness of ISO in the implementation process was well integrated into the agency's system.